Penyelesaian Tindak Pidana Pencucian Uang - Roy Saputra (Justice Legislation and Crime Journal, 2025)
Criminal acts of money laundering is a criminal offense or derivative crime is always preceded by the predicate offense, because the object of the crime of money laundering is the proceeds of predicate offenses. This has implications for the formulation of money laundering in Article 3, 4 and 5 of Law No. 8 of 2010 Concerning the Prevention and Combating of Money Laundering. Where each article contained elements of criminal acts of money laundering and treasure in the wash proceeds of predicate offenses. So it is not possible in case of money laundering stand alone without preceded by the predicate offense. In terms of substantive criminal law, the element of "known or reasonably suspected proceeds of the offenses referred to in Article 2 of the Law money laundering" must be fulfilled. Similarly, when viewed from the side of criminal law formal, that the process of investigation, prosecution and examination in court against money laundering is not obliged to prove the crime of origin in advance, can be implemented if the article is intended to seize assets from crime by using a system of deprivation in brake. If using a system of appropriation of assets in the persona, Article 69 can’t be carried out or collide with Article 3 of Law No. 8 of 2010 Concerning the Prevention and Combating of Money Laundering.